2020
DOI: 10.1159/000508098
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Spectroscopy following Mild Traumatic Brain Injury: A Systematic Review and Meta-Analysis on the Potential to Detect Posttraumatic Neurodegeneration

Abstract: <b><i>Introduction:</i></b> Traumatic brain injury (TBI) is the most relevant external risk factor for dementia and a major global health burden. Mild TBI (mTBI) contributes to up to 90% of all TBIs, and the classification “<i>mild”</i> often misrepresents the patient’s burden who suffer from neuropsychiatric long-term sequelae. Magnetic resonance spectroscopy (MRS) allows in vivo detection of compromised brain metabolism although it is not routinely used after TBI. <b>… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 59 publications
1
19
0
Order By: Relevance
“…During the acute phase of TBI, the levels of choline-comprising metabolites tend to increase, due to shearing damage to the cellular membrane. These findings were in line with Eisele et al, who reported that the choline peak on MRS is correlated with the post-TBI myelin breakdown [ 61 ].…”
Section: Changes In Choline-containing Phospholipids After Tbisupporting
confidence: 91%
“…During the acute phase of TBI, the levels of choline-comprising metabolites tend to increase, due to shearing damage to the cellular membrane. These findings were in line with Eisele et al, who reported that the choline peak on MRS is correlated with the post-TBI myelin breakdown [ 61 ].…”
Section: Changes In Choline-containing Phospholipids After Tbisupporting
confidence: 91%
“…To help identify TBI patients at risk of post-traumatic neurodegeneration, MRS has shown utility in those patients with negative routine CT and/or MRI scans, in the subacute post-injury phase (<90 days). A meta-analysis of MRS studies using N -acetyl-aspartate (NAA) as a marker of neuronal integrity and glutamate (Glu) as a marker of disturbed brain metabolism showed a reduced NAA/Glu ratio in TBI patients, primarily in the frontal lobes, indicating a possible use as a diagnostic tool [ 182 ].…”
Section: Brain Injurymentioning
confidence: 99%
“…This effect is aligned with other large-scale modeling work that showed structural disconnection associated with decreased metastability, indicating excitation–inhibition imbalance, to be related to poorer cognitive performance in TBI patients ( Hellyer et al, 2015 ). Empirical studies using MRS have also found that elevated concentrations of the neuromodulatory factor glutamate during the semiacute phase were predictive of poorer chronic outcomes ( Shutter et al, 2004 ; Eisele et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic resonance spectroscopy (MRS) is capable of detecting changes to neuromodulatory concentrations in vivo. A recent meta-analysis found evidence for elevated glutamate concentrations in adult patients after a single mild TBI (mTBI) in the acute and sub-acute phases (Eisele, Hill-Strathy, Michels, & Rauen, 2020). Furthermore, some studies have shown these elevated glutamate concentrations are predictive of long-term outcomes (Shutter, Tong, & Holshouser, 2004).…”
Section: Introductionmentioning
confidence: 99%